EXPERIENCE OF BACTERIAL TOPICAL LYSATE USE IN PRESCHOOL EDUCATIONAL ESTABLISHMENTS - T.E. Privalova; S.A. Shadrin; N.A. Shabaeva (Union of pediatricians of Russia, 2011)
Substantially higher risk of acute respiratory pathology in organized groups is well known. The authors examined 1340 preschool children and justified the usefulness of the health-improving measures, including topical application of bacterial lysate. The article demonstrates the effectiveness of this drug, as well as the short duration of its action, hence the usefulness of repeated courses of drug administration to prevent the formation of chronic infection focuses in the nasopharynx and reduce the incidence of ARI.Key words: preschool children, microbiological monitoring, health status, topical bacterial lysate in children's collective.